2021
DOI: 10.3390/ani11113016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Blastocystis sp. in Camelus bactrianus in Northwestern China

Abstract: Blastocystis sp. is an important zoonotic protist in humans and various animals with worldwide distribution. However, there have been no data on the occurrence of Blastocystis sp. in C. bactrianus, an important economic animal in northwestern China. In the present study, a PCR-sequencing tool based on the SSU rRNA gene was applied to investigate the prevalence and genetic diversity of Blastocystis sp. in 638 faecal samples from C. bactrianus in 21 sampling sites within three main breeding areas (Gansu, Inner M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
5
12
2
Order By: Relevance
“…Moreover, the current study found a higher incidence of Blastocystis infection in onehumped camels (14%) compared to two-humped camels (8%), which may be attributed to the sample size and their living conditions. Meanwhile, consistent with a previous study (Yang et al, 2021) (Hublin et al, 2021).…”
Section: Ta B L Esupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the current study found a higher incidence of Blastocystis infection in onehumped camels (14%) compared to two-humped camels (8%), which may be attributed to the sample size and their living conditions. Meanwhile, consistent with a previous study (Yang et al, 2021) (Hublin et al, 2021).…”
Section: Ta B L Esupporting
confidence: 93%
“…Dromedaries are well suited for arid habitats and serve as means of transportation, providers of milk, meat, and hides in desert regions. Bactrian camels, on the other hand, have adapted to thrive in extremely cold temperatures with limited food resources and are also utilized for transportation, milk, meat, and hides in Central Asia (Sazmand et al., 2019; Yang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…[16], and slightly higher were observed in alpacas in zoos in Sichuan, China, with 36.4% (4/11) [19]. Similar prevalence was reported in the alpacas (23.8%, 87/366) in Shaanxi, China [18], camels (133/484) in Northwestern China [21], camels (5/25) in Egypt [17], and camels (24.0%, 47/196) in Libya [12]. Many factors could explain the variation in infection rates, including host health status, management systems, population densities, age distributions, and feeding sites (Table 2).…”
Section: Discussionmentioning
confidence: 53%
“…(1), ST24 ( 14), ST25 (8), ST26 (1), ST30 (19) and one potentially novel ST (21) were identi ed in northwestern China [21]; For guanacos, two subtypes, ST10 (13) and possible novel ST22 (1), were identi ed in captive wild animals in Qinling Mountains [16].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA (gDNA) samples were isolated from oocysts of C. parvum and clinical faecal samples using a commercial kit as described [ 24 ]. Those gDNA samples for C. andersoni , C. bovis , C. ryanae , Balantidium coli , Enterocytozoon bieneusi , Blastocystis sp., and Giardia lamblia were from previous studies [ 25 , 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%